The Correlation between students' reading skill and memorizing al-Qur'an in MTs Mu'allimin Muhammadiyah Tahfizhul Qur'an - Lusi Frisia (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2022)
The aim of this research is to find out the ability of the Arabic reading skill and the ability to memorize the Qur’an among the eighth grade students in MTs Muallimin Muhammadiyah Tahfizhul Qur'an Sawah Dangka. The method of this research is descriptive and the data are shown in numbers and analyzed by the statistical method. In collecting data for this research use oral test, and sample of this research is about 30 eighth grade students in MTs Muallimin Muhammadiyah Tahfizhul Qur'an Sawah Dangka. The findings of this research are; 1) as the level of Arabic reading skill in the eighth grade is